Phenolic content and α–glucosidase inhibitory activity of herbal mixture: effect of processing technique and honey ratio - Abu Bakar Sajak, Azliana; Azlan, Azrina; Hamzah, Hazilawati; Abas, Faridah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Preparation of herbal mixtures from the traditional knowledge has been used for over centuries to improve and maintain health condition. Nonetheless, lack of scientific evaluations on regard to their bioactive metabolites as a mixture and their pharmacological effects have yet to be reported. Therefore, the objectives of this study are 1) to determine the effect of processing techniques (blending and juicing) on extracting polyphenols and 2) to determine the effect ratio of honey in herbal mixture (containing ginger, garlic, honey, apple cider vinegar, and lemon juice). Methods: Raw ingredients such as garlic, ginger, lemon and apple cider (1:1:1:1) were used as the base for this herbal mixture. The base was either blended using a blender or juiced using a juicer. The mixture was simmered (85oC - 100oC) until reduced to half of the initial volume and cooled down before being added with honey in 1:1 (rA) or 1:3 (rB) ratio. The mixtures were tested for pH, total phenolic, total flavonoid content and alpha glucosidase inhibitory activities. Results: Both of juiced samples in both honey ratio (rA and rB) have lower acidity compared to blended samples. Total phenolic content (TPC) and total flavonoid content (TFC) also showed significantly higher levels (p <0.05) in juiced samples than blended samples especially in Juicer rB. The insignificant differences in α-glucosidase inhibitory activities among mixtures indicate both extraction and ratio did not influence α-glucosidase inhibitory activities of the mixtures. Conclusion: All of the results indicate that processing techniques and ratio can affect the pH and phenolic recovery.